Arab Republic of Egypt: 2014 Article IV Consultation-Staff Report; Press Release and Statement by the Executive Director for the Arab Republic of Egypt (IMF Staff Country Reports, 2015)
KEY ISSUES The 2014 Article IV consultation takes place when the authorities have started to address longstanding economic challenges. For a number of years Egypt has suffered from low and non-inclusive growth and from high unemployment. Since 2011 these problems have been compounded by large fiscal deficits and rising public debt and by external fragility evidenced by loss of foreign exchange reserves. In 2014, Egypt adopted a new constitution and elected a new president who was candid with the electorate on the need to reform the economy. The government has developed a plan centered on structural reform and investment promotion to raise growth and create jobs, and fiscal adjustment to bring the budget deficit and public debt under control. Crucially, the authorities have already begun to implement fuel subsidy reform, raising prices by 4080 percent in July 2014.